Case report: Tongdu Xingshen acupuncture for a patient with persistent vegetative state after herpes simplex virus encephalitis - Jin, Bingxu; Tang, Yuyuan; Wu, Yunyun; Liu, Zhenhuan (Frontiers in Neurology, 2022)
Introduction: A persistent vegetative state (PVS) may be caused by traumatic or non-traumatic brain injury. PVS is a complex clinical condition with numerous complications. Nursing care, medical treatment, as well as comprehensive rehabilitation are needed to improve the outcomes of PVS. However, the prognosis remains unsatisfactory. Acupuncture therapy has been used as a rehabilitation strategy to treat PVS patients in China, which displays better outcome in consciousness recovery, intellectual ability, and motor function. Case Description: We present the case of a 4-month-long PVS after herpes simplex virus encephalitis in a 3.5-year-old boy who underwent Tongdu Xingshen acupuncture integrated with Western medicine and rehabilitation. The patient regained consciousness posttreatment. His intelligence and motor function gradually recovered after seven treatment sessions. Conclusion: Tongdu Xingshen acupuncture is a potential complementary therapy for optimizing the clinical outcome in PVS.